(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: Breast cancer is the most common gynecological malignancy in many parts of the world. It is the major cause of death for women, and its occurrence has a particular relevance to women’s health worldwide. The etiology of breast cancer appears to be multifactorial, since both. Endogenous and exogenous factors are known to increase breast cancer risk Objective: Detection of some prognostic factors in sera like LDH, ADA. Patients & Methods: Seventy-three patients with breast tumor were included in this study. Sixty-two with malignant breast cancer and 11 with benign breast tumor. The malignant breast tumor included: 8 patients with Intraductal carcinoma (IDC), 5 with Lobular carcinoma (LC), 49 patients with and infiltrative ductal carcinoma which in turn divided into 11 with well differentiated ductal carcinoma (WDC), 12 patients with moderately differentiated ductal carcinoma (MDC), and 26 patients with poorly differentiated ductal carcinoma (PDC). All cases were admitted to Al-Yarmouk Teaching Hospital and Medical City, during the period from December 1999 to January 2001. Detection of some prognostic factors in sera like Lactic acid dehydrogenase LDH, and adenosine deaminase (ADA), were detected. Results: The results indicated that serum levels of LDH were elevated in PDC (267.9±24.01) and in MDC (200.0±37.4).Other types as well as benign tumor were found within the normal range values (80-190) u/L. Serum levels of ADA were elevated in PDC type (32.7±5.21) and slightly elevated in LC. There were no significant differences between malignant types and benign breast tumor (P<0.05) whereas significant differences were recorded between healthy control and other types of tumors (P>0.05). Conclusion: The application of enzyme assay (ADA, LDH) is of prognostic value Key words: Breast cancer, ADA, LDH. Iraqi J Med Sci, 2004; Vol. 3 (1): 18-21